Organizing complexity: an inductive inquiry into algorithmic routines expansion - Timmer, Verena; Safavi, Mehdi (Academy of Management, 2024)
Routine expansion is undertheorized—we know little about how, through the expansion of the space of possible paths, routines transition in a situation of ever-increasing complexity. Using data from 6 years of participant observation and drawing insights from recent advances in process and practice research, as well as routine dynamics studies, we propose new insights on how routines expand while remain functional. Charting the transitional phases of an algorithmic routine that is undergoing a significant expansion, we describe four major biographical moments of our algorithmic routine(s) and explicate three transitional cycles between these biographical moments that enable us to develop a theoretical model for organising increasing level of complexity in algorithmic routines expansion. We make three main contributions to the extant body of research. First, as an early and revelatory study of routines expansion, we show how through expansion and contraction mechanisms, routine participants keep the routine(s) in-balance and functional, despite the ever-increasing complexity. Second, we extend research on standardization and flexibility by showing how actors purposefully limit variations in performances through not only their background knowing but also the capability to fully detach from the routine and shift to a more analytic reflection. Third, we contribute to research on routine interdependence and integration by showing how, through the design of performance objects, a single routine splits into three interdependent routines to control the space of possible paths in routine expansion.